GeoGebra integrated instruction: Effectiveness and empowerment (Siddhajyoti Interdisciplinary Journal, 2021)
Integrating ICT in mathematics instruction has been becoming the pertinent issue in Nepal. In this context, this paper explores the effect of GeoGebra embedded instruction in students learning, particularly in geometry at school level. GeoGebra is the widely used open source software which can cover almost all areas of school mathematics. So, this paper will contribute the important research findings on whether the ICT integrated instruction plays effective roles in teaching and learning mathematics. Quasi experimental design was used to conduct the study. Two parallel sets of achievement test papers, observation note and interview schedule were used to collect the data from the respondents. The data obtained from test paper was analyzed using mean, standard deviation and t-test at 0.05 level of significance. Whereas the data obtained from interview and observation wasanalysed by using general inductive approach. The result of the study indicated that the achievement score of experimental group was significantly higher than control groups after using GeoGebra in teaching mathematics.Besides, the quantitative findings, students in experimental group seemed more active and motivated during the intervention. Creativity and self-exploration are two important skills they developed after the intervention. It can be concluded that ICT embedded instruction is an effective approach for better mathematics learning